BIOLOGICAL APPLICATIONS (ANTIBACTERIAL ACTIVITY) OF BAYLIS-HILLMAN ADDUCTS DERIVED FROM BENZOXEPINE DERIVATIVES (AGAR DIFFUSION ASSAY) - Sandhyadevi Pushparaj, Vidya. A, Mohamed Haroon Basha. A, Sivakumar. N (Journal of Neonatal Surgery, 2025)
The simple an efficient protocol using a cyclic reaction for the novel synthesis of benzoxepine derivatives connecting a tandem building of C–O and C–C bonds using Baylis–Hillman adducts with paraformaldehyde under the catalist of H2SO4 was successfully realised. We also established that these 2-benzoxepine results are useful for constructing wide variety of benzoxe herecyclic compounds in very good yields. Since benzoxepines and its derivatives are well known for their biological properties, the newly synthesized benzoxepines and its derivatives also may exhibit significant bioactivities.